ANALISIS MOOD PENYIDIK DALAM PERCAKAPAN PENYIDIKAN TINDAK PIDANA UMUM DI KEPOLISIAN - Deni Indrawan; Asri Ismail; Muh. Ikbal; Daudi Richard Malusu (LP2M UIN Abdul Muthalib Sangadji Ambon, 2025)
The investigation of general criminal offenses exhibits several implementation-related phenomena, including wrongful arrests and an overreliance on eliciting confessions from examinees. This study focuses on the investigative process as reflected in the verbaal van verhoor (interrogation record). Within investigative interactions, the object of analysis is the investigator’s MOOD system. MOOD is selected because, as a linguistic resource within the interpersonal meaning domain of Systemic Functional Linguistics, it constitutes the lexicogrammatical basis through which investigators organize meaning exchange in investigative conversations in accordance with particular aims or interests. This research adopts a critical qualitative approach, employed to critically and emancipatorily uncover the realities of investigators’ language use. The study is designed as a case study, examining a general criminal case at the investigation stage within the police institution. The findings indicate that investigative conversations in this case contain 25 instances of MOOD usage by the investigator. The investigator's dominant status and the pursuit of confession drive the interaction, as shown by these results. This study makes two concrete contributions: (1) serving as a reference for the development of emancipatory investigative questioning instruments, and (2) informing the development of teaching materials for forensic linguistics courses using a Systemic Functional Linguistics approach. Future research may employ comparative units drawn from other criminal cases or specific contexts, such as doctor-patient interactions